Peraturan Daerah Syariah dan Problem Dilematis - Al Fiyah, Siti; Muhyidin, Muhyidin (JOSH: Journal of Sharia, 2023)
the results of the Reformation have made a fundamental change in the Indonesian constitutional system which initially adopted a centralized system to become decentralized. One of the effects of the implementation of the decentralization system in Indonesia is the emergence of Islamic regional regulations. Some of the contents of these Sharia Regional Regulations are contrary to the principles of human rights contained in the constitution. . In addition, this regulation appears to be related to the historicity of the implementation of Islamic Sharia in Indonesia since Islam entered the archipelago. Some of the contents of sharia regulations conflict with provisions in the principles of human rights both contained in human rights in an Islamic perspective and human rights contained in the Indonesian constitution. The main principle in Islamic teachings is the benefit of society which is contained in the Qur'an and Sunnah. Implementation of laws and regulations including regional regulations which are the lowest level in the hierarchy of laws and regulations must realize the main goal of the state, namely the protection of citizens' rights and in the concept of dusturiyah siyasah it is also stipulated that regulations must ensure the benefit of society as the main goal in Islamic nomocracy.